2021
DOI: 10.1002/jmv.27248
|View full text |Cite
|
Sign up to set email alerts
|

Lineage and sublineage analysis of human papillomavirus type 56 in cervical samples of Iranian women

Abstract: Understanding the regional lineages and sublineages of human papillomavirus type 56 (HPV 56) would be of great importance for further evolutionary, epidemiological, and biological investigations. To identify the distribution of lineages and sublineages of HPV 56 in Iran, the sequence variations of the E6 gene were analyzed in normal, premalignant, and malignant samples obtained from the cervix. In total, 58 HPV 56positive samples were investigated by nested-PCR and followed by bidirectional direct nucleotide s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Regarding the finding that lineage A of HPV 52 is prevalent in Iran, the E6 variation sequence analysis of other HPV types including HPV 16, 18, 31, 39, 45, and 56 in Iranian women showed that distinctive lineage/sublineages are dominant in this population as follows: for HPV 16 (lineage D), HPV 18 (sublineage A4), HPV 31 (lineage A), HPV 39 (sublineage A1), HPV 45 (lineage B), and HPV 56 (lineage B). 15 , 18 , 19 , 20 , 21 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the finding that lineage A of HPV 52 is prevalent in Iran, the E6 variation sequence analysis of other HPV types including HPV 16, 18, 31, 39, 45, and 56 in Iranian women showed that distinctive lineage/sublineages are dominant in this population as follows: for HPV 16 (lineage D), HPV 18 (sublineage A4), HPV 31 (lineage A), HPV 39 (sublineage A1), HPV 45 (lineage B), and HPV 56 (lineage B). 15 , 18 , 19 , 20 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…Although the distribution of HPV types is well‐known in Iran, 11 there is much less identified about HPV lineages and sublineages in this country 15,18–21 . The data in this regard is important as it would provide a rationale for future studies on their epidemiology, evolution, pathogenicity, and biology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All samples were screened for HPV by nested polymerase chain reaction (nested‐PCR) using primer pairs of MY09/11 and GP+5/+6, as described previously 23 . Briefly, 200 ng of DNA template was subjected to the amplification of a 150 bp fragment of the L1‐coding gene in a reaction mixture containing 10 pmol of each primer pair, 50 μM of each dNTP, 2 mM MgCl 2 , and 1 U of Taq‐DNA polymerase.…”
Section: Methodsmentioning
confidence: 99%
“…Some types are supposed to have existed in specific regions although it seems traveling, tourism, and social communications increase the exposure risk of HPVs' different genotypes. Therefore, the various HPV genotypes were cocirculated between the communalities 6,8,10,19,25,45,[47][48][49][50][51][52][53]. Moreover, synergistic effects and trends in cocirculation of specific HPV genotypes are needed to be appraised in a future meta-analysis study.…”
mentioning
confidence: 99%